(untitled) (Journal of Event, Tourism and Hospitality Studies, 2022)
This study identified factors that are crucial in sustaining the performance of tourism village through the village fund. Village Fund is one of the fiscal development instruments aimed at accelerating the distribution of welfare for the villages especially for tourism villages. Data used in this study includes the realization of the Village Fund in 2018 and 2019 from the Fiscal Policy Agency (BKF), Ministry of Finance. Data on the realization of the Village Fund are categorised into output codes in the form of numbers. For achieving the research objectives, the analytical tool used is Data Envelopment Analysis (DEA) to measure the efficiency level of a DMU (Decision Making Unit). The lack of efficiency in utilizing the Village Fund is influenced by several factors, including the lack of knowledge and capabilities of village officials, the lack of data base common platform, the lack of technical capability in managing administrative aspects, and the misalignment of Village Fund expenditures and the village needs or targets. The study concluded that there is a need for more substantial synergies and coordination between the central and regional governments on the common platform village fund data base to minimize the deficiencies to overcome these obstacles.